Please please please please please please please please please please please please please please please please please please tell me fastly
Attachments:
![](https://hi-static.z-dn.net/files/d1c/fed1f1e593f22c26d23d70d2a7d0a632.png)
Answers
Answered by
0
( 2a )^3 + ( 3b )^3 = ( 2a + 3b ){ ( 2a )^2 - 2a*3b + ( 3b )^2 }
8a^3 + 27b^3 = ( 2a + 3b )( 4a^2 - 6ab + 9b^2 )
8a^3 + 27b^3 = 8a^3 - 12a^2b + 18ab^2 + 12a^2b - 18ab^2 + 27b^3
8a^3 + 27b^3 = 8a^3 + 27b^3
Ans. ( 2a )^3 + ( 3b )^3 = ( 2a + 3b ){ ( 2a )^2 - 2a*3b + ( 3b )^2 } , verified.
Similar questions